Parents' Response to Distance Learning Policies - Simanjuntak, Sri Yunita; Kismartini, Kismartini (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2020)
Efforts to prevent the transmission of the Covid-19 pandemic in primary schools are to issue a Distance Learning (PJJ) policy. The purpose of this study was to see the responses of parents to distance learning policies in North Sumatra. The research method is descriptive with a qualitative approach. The data collection technique is in the form of a questionnaire that is distributed online via google form. Respondents of this study were parents at the SD / MI and SMP / MTs levels in 6 districts / cities partnering the Tanoto Foundation in North Sumatra Province. The data analysis used is descriptive percentage using pivoting. The total respondents were 278 people who were selected by simple random. The conclusion of this study is that 99.64% of parents stated that children had implemented the PJJ program; 94% of parents stated that they participated in guiding their children at home; 96% stated that they had been given instructions by the teacher in guiding the PJJ program; 65% of parents stated that they felt comfortable with PJJ activities.